Elevated temperature is more effective than elevated [CO2] in exposing genotypic variation in Telopea speciosissima growth plasticity: implications for woody plant populations under climate change. (4th July 2015) - Huang, Guomin; Rymer, Paul D.; Duan, Honglang; Smith, Renee A.; Tissue, David T.
Abstract Intraspecific variation in phenotypic plasticity is a critical determinant of plant species capacity to cope with climate change. A long‐standing hypothesis states that greater levels of environmental variability will select for genotypes with greater phenotypic plasticity. However, few studies have examined how genotypes of woody species originating from contrasting environments respond to multiple climate change factors. Here, we investigated the main and interactive effects of elevated [CO2] (CE) and elevated temperature (TE) on growth and physiology of Coastal (warmer, less variable temperature environment) and Upland (cooler, more variable temperature environment) genotypes of an Australian woody species Telopea speciosissima. Both genotypes were positively responsive to CE (35% and 29% increase in whole‐plant dry mass and leaf area, respectively), but only the Coastal genotype exhibited positive growth responses to TE. We found that the Coastal genotype exhibited greater growth response to TE (47% and 85% increase in whole‐plant dry mass and leaf area, respectively) when compared with the Upland genotype (no change in dry mass or leaf area). No intraspecific variation in physiological plasticity was detected under CE or TE, and the interactive effects of CE and TE on intraspecific variation in phenotypic plasticity were also largely absent. Overall, TE was a more effective climate factor than CE in exposing genotypic variation in our woody species. Our results contradict the paradigm that genotypes from more variable climates will exhibit greater phenotypic plasticity in future climate regimes.